Dual‐feedback digital linearisation structure with phase noise mitigation. Issue 10 (1st May 2016) - Liu, Ying; Quan, Xin; Pan, Wensheng; Tang, Youxi
Abstract : A digital predistortion (DPD) architecture is proposed to mitigate the phase noise of the local oscillator (LO). In this architecture, a novel dual‐feedback structure is designed to simultaneously capture the input and output signals of the power amplifier (PA) to perform the PA modelling and DPD linearisation, and thus relax the requirement on the LO phase noise. Experimental results validate the superior performances of the proposed linearisation architecture over the conventional DPD with LO phase noise. It is verified that the proposed DPD can achieve satisfactory performances even with low‐quality LOs of high phase noise levels.